Analysis of Financial Performance Measurement Models for Zakat Institutions - Saputra, Dodi (ITQAN: Journal of Islamic Economics, Management, and Finance, 2024)
This research aims to identify and analyze the financial performance measurement model of zakat institutions. This research uses qualitative methods, a literature study approach, and descriptive analysis. The data source comes from Google Scholar. Literature data was obtained by searching for keywords on Google and the publish or perist application. The research results show that there are five performance measurement models in Zakat financial institutions consisting of Data Envelopment Analysis (DEA), Zakat Management Organization Ratio (OPZ), Indonesian Magnificence of Zakat (IMZ), International Standard of Zakat Management (ISZM), and Balance Scorecard. The research results also found that each measurement model has its characteristics with different measurement methods. Zakat supervisory authority institutions and researchers can use five performance measurement models in Zakat financial institutions.